2006
DOI: 10.1007/s10278-005-9242-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists' Preferences for Just-in-Time Learning

Abstract: Background: Effective learning can occur at the point of care, when opportunities arise to acquire information and apply it to a clinical problem. To assess interest in point-of-care learning, we conducted a survey to explore radiologists' attitudes and preferences regarding the use of just-in-time learning (JITL) in radiology. Materials and Methods: Following Institutional Review Board approval, we invited 104 current radiology residents and 86 radiologists in practice to participate in a 12-item Internet-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…‘Just-in-time’ learning has been described in the medical literature and used for the education of physicians ( 23 26 ). The term refers to learning opportunities that are structured to be delivered exactly when and where the learner needs them ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…‘Just-in-time’ learning has been described in the medical literature and used for the education of physicians ( 23 26 ). The term refers to learning opportunities that are structured to be delivered exactly when and where the learner needs them ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the application described here can assist an ultrasound trainee in learning aspects of US, it is obviously not a substitute for "hands-on" US experience and regular practice. Even so, as the application has anytime and anywhere access, it may play a role in blended learning models where there is a demand for interactive web-based learning resources [5,14,15]. Trainees and US educators can easily organize collections of both normal and abnormal ultrasound cases which ▶ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies of mobile learning identified wasted time for students as a concern that could be addressed by allowing immediate access to information that would soon be required [30,55]. This 'just in time learning' , defined as a "brief educational experience targeting a specific need or clinical question" [78], can be facilitated through e-learning. Ten of the included studies concluded that an integrated approach works best, whereby educators do not seek to replace traditional methods but rather supplement them.…”
Section: Intervention Characteristicsmentioning
confidence: 99%